KAJIAN ISU TOLERANSI BERAGAMA, BUDAYA, DAN TANGGUNG JAWAB SOSIAL MEDIA - Digdoyo, Eko (Universitas Muhammadiyah Ponorogo, 2018)
The purpose of this study is to deepen social phenomena related to issues of religious tolerance, culture and the role of the media. Nowadays, the existence of printed, electronic, or social media is regarded as a consideration of a study. The fundamental reason is that media is currently the most important part in publishing the handling of religion, ideology, and social religious move cases within society. Generally, media is capable of stirring the order of society life. Therefore, this study has fairly important scope, specifically, in the role of publishing the moral principle of Divinity and Humanity and the practice of religion and culture tolerance. In this case media is assumed as a part of agents and social controllers, particularly in informing the value of religious freedom and protection in the community. The media also participates in reducing social-religious conflict